1981
DOI: 10.1210/endo-108-5-1795
|View full text |Cite
|
Sign up to set email alerts
|

Catecholamine Turnover Rates in Discrete Hypothalamic Areas and Associated Changes in Median Eminence Luteinizing Hormone-Releasing Hormone and Serum Gonadotropins on Proestrus and Diestrous Day 1*

Abstract: We have correlated catecholamine [CA; i.e. norepinephrine (NE), dopamine (DA), and epinephrine (E)] turnover rates in discrete hypothalamic nuclei and in the median eminence (ME), with concentration changes in ME LHRH and serum LH, FSH, PRL, estradiol, and progesterone levels at various times during proestrus and diestrous day 1 in 4-day cyclic rats. CA concentrations were measured with a radioenzymatic assay at 0, 60, and 120 min after ip injection of 400 mg/kg alpha-methyl-p-tyrosine, and rate constants and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
95
1
1

Year Published

1984
1984
2008
2008

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 201 publications
(100 citation statements)
references
References 41 publications
(41 reference statements)
3
95
1
1
Order By: Relevance
“…Hypothalamic 5-HT content varies over the estrous cycle (Rozsahegyi et al, 1973), and estrogen has been known to cause an acute biphasic up-and down-regulalion of 5-HT receptors (Biegon and McEwen, 1982). Likewise during early proestrous, estrogen increases NA and DA turnover rate in various hypothalarnic nudei induding the 52 suprachiasmatic nucleus and the median eminence (Rance et al, 1981;Wise et al, 1981).…”
Section: Constantmentioning
confidence: 98%
See 1 more Smart Citation
“…Hypothalamic 5-HT content varies over the estrous cycle (Rozsahegyi et al, 1973), and estrogen has been known to cause an acute biphasic up-and down-regulalion of 5-HT receptors (Biegon and McEwen, 1982). Likewise during early proestrous, estrogen increases NA and DA turnover rate in various hypothalarnic nudei induding the 52 suprachiasmatic nucleus and the median eminence (Rance et al, 1981;Wise et al, 1981).…”
Section: Constantmentioning
confidence: 98%
“…The pattern of LHRH content in these discrete hypothalamic areas have been shown to parallel the changes in ME LHRH content occurring during proestrous. Thus, it has been concIuded that the hypothalamic LHRH system functions as an integrated unit regulating the release of LHRH from the ME (Wise et al, 1981). The extensive distribution ofLHRH in the hypothalamus suggests that UIRH can probably affect other hypophysiotropic factors.…”
Section: Organizationmentioning
confidence: 99%
“…It should be noted that estradiol increases noradrenergic turnover before and during the proestrus LH surge in several brain areas, including the POA and median eminence (Rance et al 1981, Mohankumar et al 1994, and that an increased noradrenergic input to POA is essential for the synthesis as well as for the release of GnRH (Herbison 1997). In LC neurons, estradiol stimulates gene expression of TH and dopamine beta hydroxylase (Serova et al 2002), probably by acting through ER.…”
Section: Locus Coeruleusmentioning
confidence: 99%
“…Oestrogen and progesterone have direct and opposing actions on dopaminergic neurotransmission. Preclinically, oestrogen increases dopamine synthesis (Pasqualini et al 2005;, turnover and release (Becker and Beer, 1986), and dopamine receptor density (Hruska andSilbergeld, 1980 andRance et al, 1981b), as well as decreasing monoamine activity which reduces the degradation of dopamine (Luine et al, 1975). In contrast, progesterone appears to down-regulate dopamine systems (Shimizu et al, 1993), leading to the suggestion that the results reported in this study may be influenced by the facilitatory effect of oestrogen on the dopaminergic system during the follicular phase of the menstrual cycle.…”
Section: Discussionmentioning
confidence: 99%